Sonographic Estimated Fetal Weight among Diabetics at ≥ 34 Weeks and Composite Neonatal Morbidity - Leen Al-Hafez; Michael L. Pirics; Suneet P. Chauhan (American Journal of Perinatology Reports, 2018)
Abstract